The Effect of Thyroid Stimulating Hormone Level Within the Reference Range on In-Hospital and Short-Term Prognosis in Acute Coronary Syndrome Patients - Gürdoğan, Muhammet (Medicina (Kaunas), 2019)
Background and objectives: Despite being within the normal reference range, changes in thyroid stimulating hormone (TSH) levels have negative effects on the cardiovascular system. The majority of patients admitted to hospital with acute coronary syndrome (ACS) are euthyroid. The aim of this study was to investigate the effect of TSH level on the prognosis of in-hospital and follow-up periods of euthyroid ACS patients. Materials and Methods: A total of 629 patients with acute coronary syndrome without thyroid dysfunction were included in the study. TSH levels of patients were 0.3–5.33 uIU/mL. Patients were divided into three TSH tertiles: TSH level between (1) 0.3 uIU/mL and <0.90 uIU/mL (n = 209), (2) 0.90 uIU/mL and <1.60 uIU/mL (n = 210), and (3) 1.60 uIU/mL and 5.33 uIU/mL (n = 210). Demographic, clinical laboratory, and angiographic characteristics were compared between groups in terms of in-hospital and follow-up prognosis. Results: Mean age was 63.42 ± 12.5, and 73.9% were male. There was significant difference between tertiles in terms of TSH level at admission (p < 0.001), the severity of coronary artery disease (p = 0.024), in-hospital mortality (p < 0.001), in-hospital major hemorrhage (p = 0.005), total adverse clinical event (p = 0.03), follow-up mortality (p = 0.022), and total mortality (p < 0.001). In multivariate logistic regression analysis, the high–normal TSH tertile was found to be cumulative mortality increasing factor (OR = 6.307, 95%; CI: 1.769–22.480; p = 0.005) during the 6-month follow-up period after hospitalization and discharge. Conclusions: High–normal TSH tertile during hospital admission in euthyroid ACS patients is an independent predictor of total mortality during the 6-month follow-up period after hospitalization and discharge.